Araza (Eugenia stipitata McVaugh, Myrtaceae) a new fruit crop in the Philippines (The Philippine Journal of Crop Science, 2012)
Araza (Eugenia stipitata McVaugh), also known as Amazonian pear, araca-boi and pichi, is a member of the family Myrtaceae and is a native of tropical America. It was introduced from Brazil by the senior author in 1997 and fruited for the first time in 2001. Morphological characterization of the tree, leaf and fruit was carried out for 3 years. The average fruiting tree is 3 m high with a canopy spread of 2 m. Fruiting takes place three times a year with a total yield of 60-90 fruits per year. The tree has dark green, elliptic and pubescent leaves with very short petioles. Fruits are oblate, of medium size (120 g) with yellow, thin peel, few seeds and yellow, acidic flesh.